Nouns in apposition: Portuguese data - Rio-Torto, Graça (Linguística: Revista de Estudos Linguísticos da Universidade do Porto, 2017)
The nature of N1N2 constructions, or nouns in apposition, is controversial: depending on the theoretical framework, they can be considered as compounds or as syntactic constructions. Indeed, nouns in apposition function as a hybrid category, in a double way: the same lexical structure in apposition is viewed either as a coordinative construction, as a subordinative or as an attributive construction. N2 functions as a modifier or as an attributive item of N1; in Portuguese, when plural is syntactically mandatory, N1 (the head) is systematically pluralized; N2 either rejects inflection or behaves as a predicator, allowing inflectional marks. We claim that Romance NN behave as a specific type of compounds. This assumption is grounded on their behaviour by contrast with phrasal properties. Portuguese compounds are characterized by a narrow relationship between internal structure, headness and inflectional patterns. In Portuguese, by default, the head of compound is inflected. NN related by an attributive semantic link are nowadays particularly unstable and problematic regarding inflection. Inflectional variation — widely attested — helps in determining the status of NN in apposition: as two inflectional patterns are available, we must verify if they correspond to two different constructions or to one structure with two readings. The analysis addressed is supported by empirical data of contemporary Portuguese language extracted from Brazilian and European databases, and requires the theoretical articulation of a double predicative class of N2 (holistic and partitive) with inflectional fluctuation of attributive N2 in the second situation: performing a continuum, double inflection is close to holistic predication and single inflection (of N1) is close to partitive predication; systematic double inflection is close to coordination and inflectional oscillation is close to attribution. The predicative power of nouns in apposition supports their partitive and their holistic reading. Inflectional fluctuation of N2 illustrate in an optimistic way their hybrid nature.